HUBUNGAN KELEKATAN ANAK PADA IBU DENGAN KEMANDIRIAN ANAK USIA DINI DI KB CERIA 1 SUMBERAGUNG SUMBERMANJING-MALANG - Sumariyeh; Nurhayati (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2022)
The formation of children's independence is based on the goals that are applied, such as the pattern of attachment between mother and child associated with the form of bathing the child. The research method used is quantitative with non-experimental research. The object data were 27 children based on purposive sampling technique. The results of this study indicate that the pattern of attachment against with a moderate level of independence is shown in inconsistent treatment from the mother. The child's level of independence is shown by the child doing the task. The resulting hypothesis has a significant relationship with the correlation value rxy = 0.956 with p = 0.00 (p <0.05). The direction of the positive relationship indicates that the higher the child's independence. So, the lower the attachment of the child to the mother. With a significance level of correlation p = 0.00 (p <0.05). The research suggestion is that parents are expected to apply a family curriculum for children in order to help organize independent behavior according to the child's developmental stage.